2022
DOI: 10.1371/journal.pone.0275208
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of key Essential Nutrition Action (ENA) messages and its predictors among mothers of children aged 6–24 months in Southern Ethiopia, 2021: A community-based crossectional study

Abstract: Background Essential nutrition action(ENA) is a framework for managing advocacy, establishing a foundation, and implementing a comprehensive package of preventive nutritional activities. Essential Nutrition Actions study studies provide current information on each nutrition action, allowing health systems to focus more on nutrition, which is critical in tackling the "double burden" of malnutrition: underweight and overweight. Hence, this study aimed at assessing the level of ENA practice and its predictors amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Positive nutrition outcomes have been reported over a ten-year period across Africa attributed to nutrition education [21]. A similar study in Ethiopia showed that knowledge about nutrition interventions, in this case, ENAs was associated with higher uptake of the interventions [22].…”
Section: Discussionmentioning
confidence: 89%
“…Positive nutrition outcomes have been reported over a ten-year period across Africa attributed to nutrition education [21]. A similar study in Ethiopia showed that knowledge about nutrition interventions, in this case, ENAs was associated with higher uptake of the interventions [22].…”
Section: Discussionmentioning
confidence: 89%
“…The sample size of the study was determined using the single population proportion formula. Taking into account a 95% confidence interval (CI) and a 5% margin of error (d), along with a prevalence rate of 47.4% for the practice of key ENA messages among mothers from a study in Lemo District, Southern Ethiopia ( 27 ), and accounting in a 10% non-response rate, the final sample size was 421.…”
Section: Methodsmentioning
confidence: 99%
“…Data collected for this study were obtained through a paper-based approach. A structured, pretested interviewer-administered questionnaire was used, which was adapted from previous studies ( 26 , 27 ). Additionally, participants’ wealth status was evaluated using a tool consisting of 37 items adapted from EDHS ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations